SIRENA, une plateforme participative au service de la gouvernance du delta transfrontalier du fleuve Sénégal - Marie-Christine Cormier-Salem; Labaly Toure; Mathilde Fabre; Yasmin Bouaita; Boubacar Ba Mamadou El Abass; Élisabeth Habert (Revue d'ethnoécologie, 2016)
Coastal wetlands, ecosystems that are providing diverse services and are subjected to multiple pressures, are confronted with contradictory management policies, torn between agricultural or hydropower development and biodiversity conservation. In a context of rapid environmental and socio-economic change, this is the case for the Senegal River Delta, which became a Biosphere Reserve in 2005.Within the framework of the LMI PATEO (IRD/UGB), an Information System for the management of natural resources in the Senegal River Delta was created in order to represent the complex and dynamic issues affecting it. This tool attempts to organize a set of normalized geographical data at the scale of this transboundary area. More specifically SIRENA endeavors to be a tool for dialogue and a support for decision-making requiring a participatory approach by, in particular, involving the stakeholders who are already producing and using spatialized data. This paper will present SIRENA (concepts, actions, first results) and questions the relevance of such a participatory platform for the sustainable governance of the resources and ecosystems of the Senegal River Delta.The emphasis is on the co-construction of the platform with the various stakeholders (protected area managers, researchers, geomatics experts) through all its phases from design to implementation. The set-up involves workshops for dialogue, training, fieldwork and the use of communication tools (mailing list, file exchange). The design and data collection feeding the system are managed by mixed thematic working groups. In this manner SIRENA has established a network of partners and created a platform for multi-stakeholder dialogue, rather than only collecting data or producing new knowledge. This collaborative process, that seeks to be permanent, is now confronting the challenge of developing an action-research programme for the sustainable governance of the Senegal Delta, potentially expanding to other deltas in West Africa.